Caracterização filogenética / estrutural da família multigênica da H+ -ATPase de membrana plasmática em monocotiledôneas e análise funcional em Zea mays - Sousa, Lyndefania Melo de (2019)
Plants are continually exposed to environmental changes that may be unfavorable to their growth and development. However, they have developed over time mechanisms of tolerance to these adverse conditions. Among them, the presence of plasma membrane H+ -ATPase (MP) proton pumps that perform the pumping of protons from the cytoplasm to the extracellular environment, as well as the regulation of intracellular pH and the maintenance of ionic homeostasis. The proton pumps are encoded by a multigenic family displaying approximately eleven genes in plant species. However, studies on its gene and functional characterization are limited, so that the distribution and function of each gene member are still not well understood. Thus, the aim of this work was to analyze the phylogenetic and structural distribution of the multigenic H+ -ATPase MP in monocotyledons and evaluate in silico the expression profile of these genes in Zea mays during development and under stress conditions. For this, the gene members were identified and annotated through searches in genomes databases available in NCBI and Phytozome, using the BLAST tool. Afterwards, Gene and cDNA sequences were used to evaluate the structure of exons / introns through the Gene Structure Display Server tool. Subsequently, the deduced protein sequences were submitted to the MEGA 7.0 program for phylogenetic distribution inference. The expression profile of the genes was verified by the analysis of RNA sequencing experiments (RNA-seq) in corn plants deposited in the Sequence Read Archive (SRA-NCBI). The results revealed that H+ -ATPase MP can be encoded by a family of 5 to 18 genes depending on the species. These genes were distributed in five distinct clades named I-V, where similarities were identified regarding the structure of exons / introns present in genes clustered in each clade. In addition, in silica expression analysis revealed that most of the gene members were constitutively expressed in maize and some members were responsive to stress conditions such as pathogen infection, submersion, water deficiency and high nitrate concentrations. The genes clustered in clade I, for the most part, were downregulated, whereas, the majority of genes clustered in clades II and IV were upregulated. However, the gene clustered in clade V was not responsive to any of the conditions. The pattern of expression in the tissues during development revealed that genes belonging to clade IV (ZmPHA4 and ZmPHA4a) were predominantly expressed in pollen tissues, while the other genes presented variable expression depending on the tissue analyzed. In general, these data support the understanding of the phylogenetic distribution, gene structure and pattern of gene expression in tissues during development and under specific environmental conditions, making it possible to propose a classification of H+ -ATPases MP in monocotyledons.